The Value of Moderation in Interfaith Life (A Comparative Study of the Perspectives of Buya Hamka and Sayyid Qutb in Qs. Al-Baqarah/2: 256) - Cindy Gayatri; Abdul Muiz (Tilawah: Journal of Al-Qur'an Studies, 2026)
Given today's increasingly advanced era, religious communities face various challenges and problems, such as social conflicts based on religion, discrimination against religious minorities, interfaith intolerance, and many other frequently occurring issues. Therefore, religious moderation has become an important theme in the current social and religious context, especially amidst the rise of extremism. This study aims to analyze and compare the perspectives of Sayyid Qutb and Buya Hamka on the value of moderation in interfaith life, as reflected in QS. Al-Baqarah:256, which emphasizes the principle "There is no compulsion in religion." The research method used is qualitative analysis with a comparative approach, which examines the works of prominent figures and their interpretations of the verse. The research results show that, despite differences in approach and context, Sayyid Qutb and Buya Hamka agree on the importance of tolerance and respect for religious freedom. Sayyid Qutb emphasized the formation of an ideal society through the comprehensive application of Islamic values, while Buya Hamka focused more on the importance of dialogue and mutual respect between religious communities. These findings are expected to contribute to the understanding of Religious Moderation and its implementation in everyday life.